Religious education programs need to include a gender perspective - Castro Flores, Kattia Isabel (2021)
Since 1940, religious education is a mandatory subject in the curriculum of Costa Rica’s public education. Eight decades since that event now, it is crucial to reflect on the approaches guiding the teaching of this subject. Because religious education holds the ethical responsibility to help create a more just and equitable society, the current paper addresses the need to include a gender perspective in the religious education curriculum. By so doing, curricular contents that promote full recognition of women and their rights will stay up to date.